Road Crossings Increase Methane Emissions From Adjacent Peatland. Issue 11 (22nd November 2019) - Saraswati, S.; Strack, M.
Abstract: We conducted a multi‐year study in two boreal peatlands to determine the impacts of resource access roads on methane (CH4 ) emission from adjacent peatland. Data were collected from transects aligned perpendicular to, and on both sides of two roads, one cutting through a bog and one cutting through a fen and from reference areas at each peatland. During the growing seasons of 2016 and 2017, we measured CH4 flux, water table, and peat temperature every second week. At the bog, the road associated impacts (changes to water table, peat temperature, and vegetation cover) were visible up to 20 m on both sides of the road (disturbed areas) with CH4 emission from disturbed areas being significantly higher compared to the reference areas in both years. There were no significant differences in CH4 emissions from disturbed areas compared to reference areas at the fen due to the limited hydrologic impact of the road crossing at this site. Bog plots located upstream of the road on transects located at >20 m from culverts and closer to the road emitted significantly more CH4 (124.6‐mg CH4 ·m −2 ·day −1 ) than other disturbed (10.2 mg CH4 ·m −2 ·day ‐1 ) and reference areas (0.7‐mg CH4 ·m −2 ·day −1 ) due to shallower water table and warmer peat temperature. The road induced CH4 emissions (90.8 and 212.2 kg CH4 /year for each kilometer of road, in 2016 and 2017, respectively) indicated that road construction across peatlands enhances CH4 emissions from these ecosystems, creating an additional source of anthropogenic greenhouse gas. Plain Language Summary: Construction of resource access roads is common across the boreal region of Canada, and significant numbers of these roads are passing through peatlands. Peatlands are natural sources of methane, which is one of the important greenhouse gases. To determine the impacts of resource access roads on methane emission from the adjacent peatland, we conducted a study in two boreal forested peatlands (a bog and a fen). Our results showed that, at the bog, methane emission from disturbed areas were significantly higher compared to the reference areas. Similarly, the changes to the water table, peat temperature, and vegetation cover were visible up to 20 m on both sides of the road. In contrast, we did not find differences in methane emissions from disturbed areas compared to reference areas at the fen due to the limited hydrologic impact of the road crossing at this site. The increased methane emission from road adjacent areas indicates that road construction across peatlands enhances methane emissions from these ecosystems, creating an additional source of anthropogenic greenhouse gas. However, our study showed that aligning roads parallel to water flow when and where possible, and adequate culvert placement can help to minimize induced methane emissions. Key Points: Resource road crossings alter local hydrology and peat temperature and that may enhance methane emission from boreal peatlands We observed road induced methane emission from disturbed areas (2–20 m from road crossings) in the bog Aligning roads parallel to water flow and adequate culvert placement minimizes induced methane emissions